2002
DOI: 10.1073/pnas.142286599
|View full text |Cite
|
Sign up to set email alerts
|

A structural basis for the activity of retro-Diels–Alder catalytic antibodies: Evidence for a catalytic aromatic residue

Abstract: The nitroxyl synthase catalytic antibodies 10F11, 9D9, and 27C5 catalyze the release of nitroxyl from a bicyclic pro-drug by accelerating a retro-Diels-Alder reaction. The Fabs (antigen-binding fragments) of these three catalytic antibodies were cloned and sequenced. Fab 9D9 was crystallized in the apo-form and in complex with one transition state analogue of the reaction. Crystal structures of Fab 10F11 in complex with ligands mimicking substrate, transition state, and product have been determined at resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…The values calculated for BmrR are somewhat reduced relative to those found for ligand-specific ligand prototypes, which bury cognate ligands ca. 90% and exhibit Sc values >0.7 (19,20) (SI Appendix, Table S2). In agreement with X-ray structures of QacR and other MDR proteins, drug recognition by BmrR is dominated by apolar contacts involving aromatic and hydrophobic residues (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The values calculated for BmrR are somewhat reduced relative to those found for ligand-specific ligand prototypes, which bury cognate ligands ca. 90% and exhibit Sc values >0.7 (19,20) (SI Appendix, Table S2). In agreement with X-ray structures of QacR and other MDR proteins, drug recognition by BmrR is dominated by apolar contacts involving aromatic and hydrophobic residues (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6). The anthracene ring is stacked over a tryptophan, similar to the position of A3 in the ribozyme, with a few direct and water-mediated hydrogen bonds observed between heteroatoms on the bicyclic adduct and the amide backbone 41 .…”
Section: Comparison With Protein-catalyzed Reactionsmentioning
confidence: 98%
“…Several such antibodies have been crystallized in complex with either products or transition state analogs 36,[39][40][41] . Common features observed in these structures are the formation of hydrophobic cores lined predominantly by the side chains of tyrosine, phenylalanine, valine and tryptophan residues, and the stacking of one reactant over an aromatic residue, preferably tryptophan.…”
Section: Comparison With Protein-catalyzed Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Density functional theory (DFT) calculations were employed on models of the active site to study the interactions that can stabilize the transition state. [49] Kim et al reviewed and compared the noncovalent catalysis of Diels-Alder reactions by cyclodextrins, selfassembling capsules, antibodies, and RNAses, and concluded that-unlike enzyme catalysts-none of these hosts provide substantial specific binding of the transition states.…”
Section: Diels-alder Reactionmentioning
confidence: 99%